PEMANFAATAN ECENG GONDOK SEBAGAI PAKAN ALTERNATIF UNGGAS MELALUI REKAYASA NUTRISI DAN MEKANISASI PRODUKSI UNTUK PENGENDALIAN DEGRADASI LINGKUNGAN - Tri Harsono; Marlinda Nilan Sari Rangkuti; Suci Rahmawati; Adriana Y.D. Lbn Gaol; Rizal Mukra; Widya Arwita; Mustaqim Mustaqim; Widia Ningsih; Imelda Nababan (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2026)
This activity was carried out in Medan Marelan, with the Melati Partner Group. The main problems were the dependence on commercial feed reaching 80% of production costs and the high population of water hyacinth covering 10% of the water surface, causing flooding and ecosystem disruption. The objective of this activity was to provide an alternative through the utilization of water hyacinth as chicken feed. The activity was conducted from April to June 2026 through four stages, namely: socialization to increase partner awareness about the potential of water hyacinth; training and technology application which included structured harvesting techniques, the use of a chopper machine, a feed pellet machine, and the production of fermented feed with a formulation of 10 kg of rice bran, 10 kg of corn, 10 kg of concentrate, 10% water hyacinth (equivalent to 3.33 kg), and sufficient EM4 solution; followed by intensive mentoring to ensure feed processing skills were implemented independently; and monitoring. The results showed that 10% fermented water hyacinth feed resulted in a cost per kilogram of feed of Rp5,366, which is cheaper than non-fermented feed at Rp5,912/kg, enabling partners to save costs of Rp18,270 per 33.33 kg of feed, or approximately 9.2% more efficient. Furthermore, an increase in chicken body weight of 0.4 kg indicated that chicken performance was maintained and not significantly different from 100% commercial feed. This activity also supports the Sustainable Development Goals (SDGs). The utilization of 10% fermented water hyacinth provides a highly beneficial dual impact